2018
DOI: 10.1016/j.neuint.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of CYP17A1 and 3β-hydroxysteroid dehydrogenase in cells of the nervous system: Potential effects of vitamin D on brain steroidogenesis

Abstract: Steroids are reported to have diverse functions in the nervous system. Enzymatic production of steroid hormones has been reported in different cell types, including astrocytes and neurons. However, the information on some of the steroidogenic enzymes involved is insufficient in many respects. Contradictory results have been reported concerning the relative importance of different cell types in the nervous system for expression of CYP17A1 and 3β-hydroxysteroid dehydrogenase (3β-HSD). 3β-HSD is important in all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In this step, the dose- and time-dependent studies (from 15 min to 1440 min) on cell viability were performed with LA (from 10 μ M to 100 μ M) to determine its optimal concentration, and then this concentration (50 μ M) was maintained in all successive experiments. Then the combination with 50 μ M LA and 100 nM vitD [41, 42] was investigated in a time-course study (from 15 min to 1440 min) and then by the permeability assay to determine each specific concentration through BBB. In a second set of experiments, the role of oxidative stress was investigated by pretreatment for 30 min with 200 μ M H 2 O 2 on astrocytes [43].…”
Section: Methodsmentioning
confidence: 99%
“…In this step, the dose- and time-dependent studies (from 15 min to 1440 min) on cell viability were performed with LA (from 10 μ M to 100 μ M) to determine its optimal concentration, and then this concentration (50 μ M) was maintained in all successive experiments. Then the combination with 50 μ M LA and 100 nM vitD [41, 42] was investigated in a time-course study (from 15 min to 1440 min) and then by the permeability assay to determine each specific concentration through BBB. In a second set of experiments, the role of oxidative stress was investigated by pretreatment for 30 min with 200 μ M H 2 O 2 on astrocytes [43].…”
Section: Methodsmentioning
confidence: 99%
“…Astrocytes have the machinery to synthesize steroids, including testosterone and its metabolite estradiol, from cholesterol [44,45]. The production of estradiol from testosterone is mediated by the enzyme aromatase, whose activity has been reported to be higher in female astrocytes [46].…”
Section: Aromatase Inhibition Has Opposite Outcomes On the Regulationmentioning
confidence: 99%
“…Several reports on vitamin D actions in tissues other than brain have suggested that 1,25‐dihydroxyvitamin D 3 can influence steroid hormone synthesis, although there are few studies on this in cells of the nervous system . The studies on the effects of 1,25‐dihydroxyvitamin D 3 on steroidogenic pathways indicate varying responses in different cells and tissues.…”
Section: Vitamin D and Steroid Hormone Action In The Nervous Systemmentioning
confidence: 99%
“…It was proposed that oestrogen biosynthesis within the brain may be selectively modulated depending on cell type. Emanuelsson et al investigated the expression of several steroidogenic enzymes, including aromatase, in human neuroblastoma SH‐SY5Y cells and primary cultures from rat brain. In these cultures, 1,25‐dihydroxyvitamin D 3 did not influence aromatase expression.…”
Section: Vitamin D and Steroid Hormone Action In The Nervous Systemmentioning
confidence: 99%